Prevenção de infecções do trato urinário associadas a cateteres em idosos: relato de projeto de estudo multicêntrico - Paiva, Miriam [UNESP] (2015)
Patients over 65 years have higher mortality rates, longer length of hospital stays, increased functional decline and care-home placements associated with the development of Hospital Acquired Infections (HAIs). This places a significant economic and social demand on healthcare systems, patients and carers. By facilitating training and skill transfer from the UK to Brazil we intend to build capacity to produce excellent research, reduce the social and economic demand and establish long term research links to share learning and provide sustainable benefit to the UK and Brazilian research community. The aim of this report is to describe the experience of designing and developing a multicenter research project between Brazil and the United Kingdom: "How to prevent urinary tract infections associated with catheters (ITUAC) in patients over 65 years," which obtained funding for its first phase by Newton Fund of the British Academy. An initial workshop sponsored by EEUSP, FAPESP, British Council allowed the meeting of young researchers and stimulated the development of the project. Careful planning of actions in long-term held for the design of research encourages group members to keep in frequent contact via webmail and web conferencing. We intend to pursue this unique opportunity for mutual learning in order to contribute to preventing the development of IRAS in elderly patients, particularly urinary tract infections associated with catheter. New funding will allow the group to advance knowledge sharing to improve the capacity for qualitative research and more detailed understanding of infection control systems of both countries.